The Relationship Between Risk Factors and EGFR Mutation in Lung Adenocarcinoma Patients - Kusumawardhani, Erna; Paramita Yasir, Andi (Syntax Literate, 2025)
Several clinical characteristics are associated with a high frequency of aktivasi mutasi EGFR. The prevalence of EGFR mutation in different clinical characteristic subgroups can affect the success of EGFR-TKI therapy. This study aims to determine the relationship between risk factors and mutation EGFR in Pulmonary adenocarcinoma patients. This was a cross-sectional study. Secondary data were collected from medical records of pasien adenokarsinoma paru treated between 2020–2022. Patients were subjected to EGFR mutation testing, with total sampling and inclusion criteria based on known mutation results and complete medical records. Risk factors studied include gender, age, ethnicity, smoking status, history of chronic lung diseases, family cancer history, and carcinogenic exposure. Data analysis was carried out through tabulation, while tests for normality, chi-square, Fisher exact, T-test, or Mann-Whitney were applied, with significance set at p<0.05. The results showed that 64 patients with Pulmonary adenocarcinoma were subjected to Mutation testing of EGFR, with an age distribution ranging 20–80 years, a male dominance (64.1%), and age <60 years (65.6%). Smoking status had a significant association with mutation occurrence of EGFR. Non-smokers had a higher probability of having mutasi EGFR, while smokers tended to be in the wild type of group, with a significant difference (p=0.046). Other risk factors such as gender, age, ethnicity, COPD, TB, family history of malignancy, and carcinogenic exposure did not affect EGFR mutation. The clinical characteristics of Pulmonary adenocarcinoma patients at RSUD Ulin between 2020–2022 showed a significantly high level of EGFR mutation in smokers (OR=0.703).